A new Umbopilio species from Assam, NE India (Opiliones: Sclerosomatidae: Gagrellinae) - Klimeš, Leoš (Zootaxa, 2006)
The monotypic genus Umbopilio Roewer, 1956 (Opiliones, Sclerosomatidae) from Burma, originally placed in the Phalangiinae and later transferred to the Sclerosomatinae, is here transferred to the Gagrellinae. A second species of the genus, Umbopilio martensi n. sp., is described from Assam, NE India.